The Relationship between Drinking Water Consumption, Nutritional Status and Workload with The Incidence of Heat Strain in Tofu-Making Workers in West Kekalik Sub-District - Ayu, Baiq Fathin; Kardi, Kardi; Wanda, Janur (Universitas Pendidikan Mandalika, 2024)
Various cases of accidents and occupational diseases, as well as other health problems are often caused by unqualified work environment factors, Workers in a hot environment are one of the causes of workers experiencing occupational diseases. Heat strain is an acute or chronic impact caused by exposure to heat stress experienced by a person from physical and mental aspects. The physical impact caused by heat strain ranges from mild complaints such as skin rashes to fainting to life-threatening situations when there is a cessation of sweating and heat stroke. Tofu making is one of the hot working environments. This study uses a quantitative method with a sampling technique using a purposive sampling technique. The sample in this study is 44 tofu makers. The data collection technique uses questionnaires and pulse measurement. Data analysis uses the Spearman Rank test. The results showed that there was a relationship between drinking water consumption and heat strain activity with a value (p = 0.000), there was no relationship between BMI (p = 0.113) and there was a relationship between workload and heat strain incidence (p = 0.000) and heat strain complaints in tofu factory workers. It is expected that workers consume >11 glasses of drinking water and use clothes that can reflect heat such as wearing thin clothes, wearing loose shirts and easily absorbing sweat.